First record of Stenophysa marmorata (Guilding, 1828), Gastropoda, Physidae in rivers of Loja province, Ecuador - Palacio-Villamagua, Gabriela; Iñiguez-Gallardo, Verónica; Correoso-Rodríguez, Modesto (ACI Avances en Ciencias e Ingenierías, 2022)
We present the first written record of the freshwater gastropod Stenophysa marmorata in Loja, Ecuador, a specimen collected in the rivers of the city of Loja. It is known that there are many species of freshwater molluscs that can be potential bioindicators of water, thus highlighting the importance of the contributions of this research for the knowledge of the malacological fauna of Ecuador.